60‐5: Late‐News Paper: External Quantum Efficiency of All InGaN Polychromic MicroLEDs - Moran, Brendan; Armitage, Rob; Ren, Zhongmin; Kim, Hee Jin; Shchekin, Oleg (SID International Symposium Digest of technical papers, 2024)
This paper reports on the performance results including radiance, dominant wavelength, and forward voltage of monolithic MicroLEDs that can emit red, green, and blue light simultaneously and are thus described as polychromic. Further, flip chip devices have been fabricated to facilitate absolute EQE external quantum efficiency (EQE) measurements. The peak EQE for a 20 × 17 µm device are 2.0 % in red, 14.2% in green, and 17.5% in blue.